Spatial Characteristics and Influencing Factors of Human Settlement Environment in the Kuye River Basin - Zhonghua ZHANG; Hao WU (Fengjing Yuanlin, 2025)
ObjectiveThe Kuye River Basin (the “Basin”) is one of the typical basins in the arid and semi-arid areas in the middle reaches of the Yellow River. Under the human settlement development mode driven by the energy industry, the water supply shortage, serious soil erosion, incoordination between urban space and water space, and water resources pollution in the Basin are becoming increasingly prominent. From living by water and grass of early human beings to today’s “Four Determinations Based on Water”, the complex relationship between people and water is an important clue for the formation and development of human civilization, and the harmonious relationship between people and water in river basins is an important basis for achieving sustainable development. Exploring the complex relationship between human settlement environment and hydrological environment in the Kuye River Basin from the perspective of human – water relationship is helpful to guide the harmonious symbiotic development of human settlement environment and hydrological environment in the Basin, and then promote the high-quality development of human settlement environment in the Basin.MethodsThe evaluation system for the quality of human settlement environments in sub-basins has been established, with the weight of each index factor determined using the entropy method. This approach aims to elucidate the spatial characteristics of human settlement environment quality within the sub-basins of the Kuye River Basin. Utilizing ArcSWAT 2012 software, hydrological simulations are conducted for the Kuye River Basin. Input data includes DEM (digital elevation model) data, soil type data, and meteorological information specific to the basin, enabling the simulation and acquisition of hydrological factors such as sub-basin boundary and river network grade. Geographical detector is a method employed to identify spatial differentiation and uncover its underlying driving forces. By selecting optimal parameters, geographical detector is utilized to examine influencing factors on the quality of human settlement environment in the Basin from various perspectives: scale, quality, and form of the hydrological environment. The primary factors influencing spatial differentiation in the quality of human settlement environment are analyzed based on results obtained from both single-factor detection and interactive detection methods.ResultsThe spatial differentiation in the quality of human settlement environment in the Kuye River Basin is characterized by “local core agglomeration, and descending in all directions along the main river channel”, and the potential of optimizing the quality of human settlement environment in each sub-basin is very different. The shape and development degree of river network are the core factors influencing the human settlement environment in river basin. The quality of human settlement environment in river basin can be optimized by adjusting the density and length – width ratio of river network. The coupling relationship between scale, quality and source and sink of water resources is the main factor influencing the quality of human settlement environment in a basin. The systematic balance of scale, quality and source and sink of water resources should be considered in the development of human settlements in a basin to avoid the deterioration of water resources caused by excessive interference in a certain aspect. The roundness and length – width ratio of a basin are the secondary factors influencing the human settlement environment in the basin. The balanced and concentrated sub-basins are conducive to the formation of abundant water resources and efficient settlement spatial structure. Basin terrain is an important factor influencing the human settlement environment in a basin, and the impact mode on the quality of the human settlement environment in a basin is “weak monomer, strong synergy”. The terrain factors need to cooperate with river network form, water resource scale and other factors to play a role.Conclusion1) There exists significant spatial differentiation in the quality of human settlement environment in the Kuye River Basin. 2) The quality of human settlement environment in the basin is the result of long-term coupling of multiple factors such as hydrological scale, hydrological form, hydrological quality and watershed topography. 3) There is a complex interaction between the human settlement environment and the hydrological environment in the basin. The quality of human settlement environment in the basin should be improved and optimized based on the harmonious relationship between human and water, and the relationship between human and water in the basin should be optimized from multiple aspects, such as the optimization of water resource supply and demand, the regional planning of water resources, the coordinated balance of water resources within the human settlement environment and the coupling of human and water space, so as to promote the high-quality development of the human settlement environment in the Basin. With sub-basin as the basic unit, the optimization strategy of human settlement environment is determined according to local conditions.